Web 2.0 in e-Learning - M. Tariq Banday (European Alliance for Innovation (EAI), 2013)
Web 2.0 tools have created fresh opportunities for governments, education, businesses and individuals to enhance efficiency and improve effectiveness while executing respective professional duties. The key features of these tools include online character and access through a web browser, supportive for open content licenses, open sharing and social interaction, and often free to use or support free features. These have created novel prospects for teachers to combine face-to-face teaching and online materials via social media such as discussion forums, blogs and wikis. The web 2.0 educational design is based on socio-cultural learning theories such as interaction, joint creation of content, critical thinking, learning by doing and collaboration. This paper makes an appraisal of ICT adoption in education, emergence of Web, improvements in Web and its effect on the e-Learning. It explains gradual integration of ICT into education through various stages. The paper presents the content and communication dimensions of e-learning for its classification. It discusses various opportunities created by Web 2.0 tools in education for effective teacher-learner, learner-learner and teacher-teacher communication, interaction and collaboration. It presents various cases and projects involving use of some Web 2.0 tools for enhancing learning. Furthermore, it lists some challenges for successful implementation of e-learning through Web 2.0 tools and discusses some possible solutions for its control.